Pollution and its impact on cardiovascular health - Kamath, Vinay; Cantor, Gregg (International Journal Of Community Medicine And Public Health, 2025)
Cardiovascular disease is the leading cause of mortality globally accounting for about 18 million deaths annually with more with more than 3 million occurring in low and middle-income countries. There is increasing body of data supporting pollution as leading cause of morbidity and mortality. The WHO estimates that almost 99% of the world population is exposed to risk of air pollution that are higher than the ambient recommended levels. The risks are dramatically increased in developing countries. There is an increasing body of data supporting pollution as a significant contributor to cardiovascular disease. In addition to being an increasing cause of deaths annually, the economic losses are estimated to be more than 4 trillion dollars. This review focuses on air, soil, water, and noise pollution and the harmful effects they create on the cardiovascular system. These effects on people can be mitigated on an individual and societal level, which will cause improvement of cardiovascular health. There is an urgent need to increase awareness of this issue and to implement population-based strategies to reduce this risk.